Pelaksanaan Sewa Menyewa Keyboard - Nasution, Diah Lestari; Harahap, Ikhwanuddin; Siregar, Khoiruddin Manahan (Jurnal El-Thawalib, 2021)
Lease (Ijarah) is taking benefits from an object, in other words the occurrence of a moving rental event is only  the benefit of the object being rente. The problem in this research is how to implement keyboard rental in Sipange Julu Village, Sayurmatinggi District. Judging from the Sharia Economic Law Compilation on the implementation of keyboard entertainment rentals in Sipange Julu Village, Sayurmatinggi District. This research is a field research or also called empirical research. Empirical research means research that looks at the phenomenon of community law or social facts that exist in society. There are two sources of data, namely primary and secondary, while the data collection instruments are interviews, observation and documentation. Keyboard owner is in default state. namely by not bringing one of the tools if something happens such as a generator and there is a lack of time, in providing wages or payments the keyboard owner does not want to reduce payments or wages this is because in the Compilation of Sharia Economic Law Article 317 explains that the excess time musta'jir must be paid with an agreement between the two parties, this explanation can be concluded if the rental time is more then the musta'jir will pay the extra time, and if the rental time is still less than agreed, the landlord will deduct wages or payments from the lease.